2020
DOI: 10.1109/access.2020.2978891
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Provably Secure Anonymous User Authentication Scheme for Patient Monitoring Using Wireless Medical Sensor Networks

Abstract: Wireless medical sensor networks (WMSNs) are playing an increasingly important role in smart healthcare applications. Since the data transmitted in WMSNs is closely related to patient's life and health, and considering the resource-constrain feature of the sensor node, constructing an authentication scheme for WMSNs is a formidable task. Recently, Soni et al. presented an elliptic curve cryptosystem based three-factor authentication scheme for WMSNs. However, we discover that their scheme suffers from serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 40 publications
(61 reference statements)
0
32
0
Order By: Relevance
“…The scheme is specified under two back-ends of AVISPA using Security Protocol Animator (SPAN) 70,73 namely OFMC and CL-AtSe which are broadly used in various security schemes. 41,46,56,57,68,70,74 As mentioned above, the specified code in HLPSL is converted into IF to generate the final report. The Output Format (OF) of the generated report is structured as stated below.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The scheme is specified under two back-ends of AVISPA using Security Protocol Animator (SPAN) 70,73 namely OFMC and CL-AtSe which are broadly used in various security schemes. 41,46,56,57,68,70,74 As mentioned above, the specified code in HLPSL is converted into IF to generate the final report. The Output Format (OF) of the generated report is structured as stated below.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In the same year, Soni et al 45 demonstrated the Challa et al scheme 37 was weak against the session key revelation and forgery attack and also introduced a mutual authentication and session key negotiation scheme. However, this scheme did not preserve perfect forward secrecy and suffered from a sensor node capture attack as stated by Guao et al 46 in 2020. Very recently, González et al 47 developed a key management and authentication scheme for heterogeneous WSN which was provably secure, flexible and competent.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the attacker can easily calculate the session key; secondly, the attacker may destroy the normal connection process between the user and the sensor node; thirdly, the user reregistration process does not consider the issue of the revocation of the old smart card, which may cause the smart card flood. In 2020, Xu et al [32] introduced chaotic maps and rabin cryptosystem to improve Soni et al's scheme [31], providing a higher level of security and less computational consumption, which is more suitable for WMSN. Besides, Yazdinejad et al [33] shortened the time for authentication in the hospital network by using the idea of blockchain.…”
Section: Introductionmentioning
confidence: 99%